Thermophilous fringe communities as an indicator of vegetation changes: a case study of the “Murawy Dobromierskie” steppe reserve (Poland) - Szygendowski, Tomasz; Brzeg, Andrzej (Biodiversity: Research and Conservation, 2016)
In this paper, changes of the non-forest xerothermic vegetation of the “Murawy Dobromierskie” steppe reserve which occurred in the period 1993-2012 are examined. The material comprises 50 relevés, of which 43 date from 2012 and the other 7 - from 1993. Reléves were arranged in 5 analytic tables. A synoptic table was also compiled, and for each syntaxonomical species group distinguished, values of the cover coefficient (C), the collective group share index (G), and the systematic group value (D) were estimated and compared. On the basis of the obtained results, a significant decline in abundancy and/or constancy was observed within the following groups: Ch. Artemisietea vulgaris, Ch. Cirsio-Brachypodion pinnati, Ch. Festuco-Brometea, Ch. Geranion sanguinei, Ch. Koelerio-Corynephoretea, and Ch. Origanetalia and Trifolio-Geranietea sanguinei, whereas for the taxa of the Rhamno-Prunetea, a notable increase in the share of the reserve vegetation was recorded. A sizeable expansion of the moss layer was also observed in this period. The results are discussed with special regard to differences in the methodical background of both field studies.